(untitled) (Architecture Image Studies, 2025)
Within higher education, Problem-Based Learning has been embraced as a pedagogical practice that offers great promise to educators, especially in legal studies, but also in public administration-type courses. This study outlines the implementation of PBL in the Administrative Law teaching with the outcomes that PBL promoted active student learning, improved students’ problem-solving skills, and built a deeper familiarity with legal knowledge. By applying theories to specific cases, students draw on theory and practice to enhance their understanding of administrative law. Moreover, collaboration in teamwork helped build communication skills, critical thinking skills, logical reasoning skills, and creativity. While existing studies have found PBL to be effective as a pedagogy in legal settings and other content areas, limitations in sample size and duration limit generalizability. Future studies should extend PBL implementations over time and with variety that may offer further evidence of sustained impacts of PBL.